스케일링 건강보험 확대에 대한 일반인과 치과위생사의 인식도 조사 - 주온주; On Ju Ju; 강은주; Eun Ju Kang; 우승희; Seung Hee Woo; 이아주; A Ju Lee; 이혜정; Hea Jung Lee; 박미연; Mi Yeon Park (Han'guk Ch'iwisaeng Hakhoe chi, 2014)
Objectives : The purpose of the study is to investigate the recognition between laypersons and dental hygienists on expansion of health insurance of scaling. Methods : A self-reported questionnaires was filled out by 100 laypersons and 100 dental hygienists from October 7, 2013. Data were analyzed by SPSS version 21.0 program. Results : All the dental hygienists recognized the introduction of the health insurance of scaling and 71.0% of the laypersons agreed. The introduction of health insurance of scaling was responsible for the interest toward scaling in 80 dental hygienists(80.0%) and 66 laypersons(66.0%). 94% of dental hygienists answered that health insurance of scaling would prevent periodontal diseases. The expansion of health insurance of scaling revealed many periodontal diseases and 52% of laypersons answered that prevention of periodontal diseases would deprive the dental hygienists of their jobs. Conclusions : The expansion of health insurance of scaling can prevent the periodontal diseases and enhance the oral health services. So the government must try to expand the health insurance of scaling.